DOI: 10.47749/t/unicamp.2011.837880
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias de aprendizagem e de regulação emocional de estudantes dos cursos de formação de professores

Abstract: A concretização deste sonho ocorreu, porque diversas pessoas acreditaram em mim, motivaram e contribuíram efetivamente para que este momento se consolidasse. Sinto-me orgulhosa pela conquista.A escrita e a pesquisa acadêmica, por muitas vezes, constitui um processo solitário, porém, se olharmos ao nosso redor, sempre encontraremos pessoas solícitas, que nos incentivam e estão dispostas a nos apoiar. Por isso, preciso agradecer:A Deus, pela vida e pela força espiritual.À Faculdade de Educação da Universidade Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 65 publications
1
5
0
1
Order By: Relevance
“…Besides gender differences in strategies to deal with anxiety, other studies have, however, pointed out higher reports of learning strategy use among female students in all LASSI scales (Bartalo & Guimarães, 2008 ), in note taking, in note reviewing, in planning lists, and in environmental structuring (Lins, 2013 ) and planning strategies (Silva et al, 2016 ). No differences between genders in the report of the use of learning strategies were found, as well as in other studies (Bortoletto, 2011 ; Martins, 2016 ).…”
Section: Literature Reviewsupporting
confidence: 71%
See 3 more Smart Citations
“…Besides gender differences in strategies to deal with anxiety, other studies have, however, pointed out higher reports of learning strategy use among female students in all LASSI scales (Bartalo & Guimarães, 2008 ), in note taking, in note reviewing, in planning lists, and in environmental structuring (Lins, 2013 ) and planning strategies (Silva et al, 2016 ). No differences between genders in the report of the use of learning strategies were found, as well as in other studies (Bortoletto, 2011 ; Martins, 2016 ).…”
Section: Literature Reviewsupporting
confidence: 71%
“…Also, for the concentration scale, students who were in the middle of their course of study had significantly higher scores than those in their initial semesters. Studies such as those of Boruchovitch et al (2020), Bortoletto (2011) and Endo et al (2017) also identified higher levels of learning and study strategies in students in the initial semesters. However, results from research carried out by Marušić et al (2017), Ribeiro and Silva (2007) and Silva et al (2016) were contrary to those of the present study, revealing that students of more advanced semesters reported using more learning and study strategies than did those who were in the initial semesters.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…No entanto, os resultados de pesquisas sobre estratégias de aprendizagem realizadas nos últimos anos do século XX e nas duas décadas do século XXI em diferentes níveis de ensino a nível internacional (Lopes, 1997;Boruchovitch, 1999;Tavares et al, 2003;Muneiro, 2008;Lemos, Costa, & Barbosa, 2009;Bortoletto, 2011;Oliveira, Boruchovitch, & Santos, 2011;Cunha & Boruchovitch, 2012;Perassinoto, Boruchovitch, & Bzuneck, 2013;Scacchetti, Oliveira, & Moreira, 2015;Prates, Lima, & Ciasca, 2016;Castro, Miranda, & Leal, 2016;Goya, Rodriguez, Araújo, & Venero, 2017;Beluce & Oliveira, 2017;Góes & Alliprandini, 2019;Zhang, Thomas, & Qin, 2019;Boruchovitch, Góes, Acee, & Felicori, 2020), têm revelado que os estudantes nem sempre apresentam um repertório diversificado de estratégias de aprendizagem e aqueles que as apresentam não as utilizam com frequência e regularidade. Esses resultados têm também revelado que a intervenção para utilização de estratégias de aprendizagem tem sido bem-sucedida, de modo geral, produzindo melhoria no rendimento escolar dos alunos.…”
Section: Introductionunclassified